2014
DOI: 10.4103/2229-516x.136780
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge, use and attitude toward multivitamin supplementation: A cross-sectional study among general public

Abstract: Background and Objective:The use of supplements has increased substantially in the past few decades. The present study is an effort to explore pattern of use, knowledge and attitude toward consumption of multivitamin supplements among the general public.Materials and Methods:A descriptive cross-sectional study on 120 adult participants from the general public was conducted. The participants were interviewed and information was collected in a predesigned structured questionnaire. The data was analyzed and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 25 publications
4
37
0
3
Order By: Relevance
“…Researchers in India [16] found that the use of multivitamins was highly prevalent among the public and most of them were unaware with their possible harm or interactions. In accordance with the latter finding, a considerable number of participants in both recent surveys had the belief that these drugs like food and unaware with the health hazards which may result as a consequence of their over consumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in India [16] found that the use of multivitamins was highly prevalent among the public and most of them were unaware with their possible harm or interactions. In accordance with the latter finding, a considerable number of participants in both recent surveys had the belief that these drugs like food and unaware with the health hazards which may result as a consequence of their over consumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this is one of the most frequent reasons for consumption given by supplement users. An enhanced feeling of well-being, a reduction in mental and physical fatigue and improvements in psychological and cognitive functions are also among the commonly reported motivations for taking supplements [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…About 70% of the general population believes that vitamin and mineral supplementation can help to maintain health, and some studies have reported that supplementation improves subjective stress, mild psychiatric symptoms, anxiety, and fatigue [15,16].…”
Section: Discussionmentioning
confidence: 99%